2010
DOI: 10.1097/eja.0b013e32833b3504
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effectiveness of different volume replacement therapies in postoperative hypovolaemic patients

Abstract: In postoperative hypovolaemic patients, lactated Ringer's solution can significantly improve haemodynamics at the end of volume loading, but this effect completely disappears at 120 min. Ten millilitres per kilogram of colloid bolus (especially HES) improved the haemodynamics at 120 min; however, this was by only 5-25% compared with baseline. The colloids caused significantly larger AUCs than lactated Ringer's solution, but only in the cardiac index, GEDVI and DO2I, plus human albumin in the SVV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
3

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 36 publications
0
41
0
3
Order By: Relevance
“…Similar results (crystalloid: colloid; 1:1.45) were noted in septic patients in the VISEP study where the goals of hemodynamic optimization were adjustments in HR, MAP, CVP and mixed venous oxygen saturation (5,20). Nevertheless, a recent study performed in an early postoperative period showed that while using the same amounts of different solutions, colloids are more effective in increasing cardiac fi lling, output and oxygen delivery than administration of Ringer's solution (21). Interaction between amounts of administered fl uid and vasoactive agents was not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results (crystalloid: colloid; 1:1.45) were noted in septic patients in the VISEP study where the goals of hemodynamic optimization were adjustments in HR, MAP, CVP and mixed venous oxygen saturation (5,20). Nevertheless, a recent study performed in an early postoperative period showed that while using the same amounts of different solutions, colloids are more effective in increasing cardiac fi lling, output and oxygen delivery than administration of Ringer's solution (21). Interaction between amounts of administered fl uid and vasoactive agents was not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Direct comparison of 6% HES 130/0.4 and 5% human albumin in adult surgical patients is scarce. Gondos et al (2010) [10] compared the hemodynamic effects of 6% HES 130/0.4, 5% human albumin, 4% gelatin and Ringer's lactate in a fluid challenge with 10 ml/kg infused within 30 minutes in postoperative hypovolemic patients. They concluded that the hemodynamic effects of 6% HES 130/0.4 were at least similar to 5% human albumin.…”
Section: In Patients Undergoingmentioning
confidence: 99%
“…This syndrome has been reported to cause a high incidence of morbidity and mortality, involving up to 90 % of the affected patients, depending on the extent of the involved lung regions [9][10][11][12][13]. Inhalation of the gastric contents into the lower respiratory tract induces a number of pulmonary syndromes, described originally by Mendelson et al, including acute aspiration pneumonitis caused by the acidity subsequent to chemical injury [14], and aspiration pneumonia resulting from the inhalation of pathogenic bacteria [7,8,15].…”
Section: Aspiration As Source Of Respiratory Morbiditymentioning
confidence: 99%
“…Among the respiratory adverse effects during anaesthesia and intensive care, bronchoaspiration poses a major challenge for health professionals [7,8]. This syndrome has been reported to cause a high incidence of morbidity and mortality, involving up to 90 % of the affected patients, depending on the extent of the involved lung regions [9][10][11][12][13].…”
Section: Aspiration As Source Of Respiratory Morbiditymentioning
confidence: 99%
See 1 more Smart Citation